(untitled) (Damascus University Journal of arts and humanities sciences, 2022)
The essence of this research is to know the extent of the use of students of the Faculty of media at the Damascus University to YouTube and motives of use and satisfactions achieved as a result of this use, study habits and usage patterns, and the extent of their employment and benefit for self-learning and skill acquisition process. The importance of the research for being new and authentic research in the field of new media and citizen journalism at the local level, and the importance of YouTube as an important means of communication have not been subject of scientific research and study in Syria. This research is considered an exploratory study of a constituent of the relationship of media students with YouTube as a means of self- learn and acquire skills.The most important results: YouTube is part of the daily life of students for the features enjoyed by this site, particularly education and training. The research has shown that about 80% of respondents are using YouTube to get information permanently, and 72% of them use it to increase their skills by learning educational and scientific programs and to learn foreign languages. The research has shown that 84 % of respondents pursuing educational content on YouTube, and that’s what helps them in self-learning and skill acquisition process. The research also showed that 72% of respondents they could get on satisfactions to identify the most important skills through YouTube, and that 84% of them could get on satisfactions to escape from the problems of the university and the lack of concrete in the practical side.